Human security - Harnisch, Sebastian; Kim, Nam-Kook (The European Union’s security relations with asian partners, 2021)
Human security emphasises additional protection and expanded freedoms for individuals: the freedom from want, the freedom from fear and the freedom to take action on one’s own behalf. The idea of combining security and human rights can be construed as a ‘narrow version’ of human security. In the EU, human security as a policy concept is currently interpreted as an umbrella term, highlighting concerns about physical integrity and equal participation rather than economic development, reflecting the EU’s recent turn towards post-conflict reconstruction and humanitarian assistance missions. In contrast, many governments in East Asia have traditionally asserted security concepts safeguarding internal and external sovereignty, thereby limiting human security claims favouring the individual and its wants. As a consequence, a considerable potential for pragmatic cooperation between East Asia and the EU is apparent, as long as this cooperation remains functionally limited and de-politicised with regard to sovereignty concerns.
Gesehen am 05.06.2023